Survival of Staphylococcus pseudintermedius in modified Romanowsky staining solutions. Issue 4 (3rd May 2017) - Misan, Angus; Chan, Wei Yee; Trott, Darren; Hill, Peter B.
Abstract : Background: Stains that are used regularly for patient‐side diagnosis to rapidly identify bacterial and fungal infections could become contaminated by common pathogens, such as Staphylococcus pseudintermedius, during slide immersion. Hypothesis/Objectives: To determine whether the inoculation of S. pseudintermedius into modified Romanowsky type stains (Quick Dip ® ) results in viable bacterial contamination and whether this is influenced by the addition of organic debris (canine hair and skin). Methods: A clinical isolate of S. pseudintermedius was inoculated into clean and organically contaminated Quick Dip ® solutions (methanol fixative, eosin, methylene blue), and positive (broth) and negative (bleach) controls. Each solution was tested for the presence of viable bacteria by counting the number of colony forming units (CFU/mL) at various time points. Solutions also were examined under high power microscopy to count the number of visible bacteria at each time point. Results: Staphylococcus pseudintermedius was able to survive in the clean and contaminated Quick Dip ® stains for at least one hour, but by 24 h no viable bacteria remained. Survival of the bacteria was not supported in the fixative at any time point. Staphylococcus pseudintermedius remained visible under high power microscopy for up to 2 weeks in all organically contaminated solutions of the Quick Dip ® set. Conclusions and clinical importance: Staphylococcus pseudintermedius only remains viable in eosin and methylene blue for short periods of time, but the prolonged visibility of dead organisms could theoretically lead to the misdiagnosis of cytology samples. Abstract : Background – Stains that are used regularly for patient‐side diagnosis to rapidly identify bacterial and fungal infections could become contaminated by common pathogens, such as Staphylococcus pseudintermedius, during slide immersion.Hypothesis/Objectives – To determine whether the inoculation of S . pseudintermedius into modified Romanowsky type stains (Quick Dip ® ) results in viable bacterial contamination and whether this is influenced by the addition of organic debris (canine hair and skin).Results – Staphylococcus pseudintermedius was able to survive in the clean and contaminated Quick Dip ® stains for at least one hour, but by 24 h no viable bacteria remained. Survival of the bacteria was not supported in the fixative at any time point. Staphylococcus pseudintermedius remained visible under high power microscopy for up to 2 weeks in all organically contaminated solutions of the Quick Dip ® set.